2009
DOI: 10.5194/acp-9-8949-2009
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in biomass burning aerosol light absorption upon humidification: roles of inorganically-induced hygroscopicity, particle collapse, and photoacoustic heat and mass transfer

Abstract: Abstract. Smoke particle emissions from the combustion of biomass fuels typical for the western and southeastern United States were studied and compared under high humidity and ambient conditions in the laboratory. The fuels used were Montana ponderosa pine (Pinus ponderosa), southern California chamise (Adenostoma fasciculatum), and Florida saw palmetto (Serenoa repens). Information on the nonrefractory chemical composition of biomass burning aerosol from each fuel was obtained with an aerosol mass spectromet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
124
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(132 citation statements)
references
References 53 publications
5
124
2
Order By: Relevance
“…Garland et al (2007) parameterized the relative humidity dependence of light extinction at 532 nm for inorganic ammonium sulfate aerosols, Baynard et al (2006) looked at mixtures of NaCl and ammonium sulfate with a few dicarboxylic acids, and Fierz-Schmidhauser et al (2010) measured the scattering dependence of ammonium sulfate and sodium chloride. Conversely, we could only find two recent studies (Hasenkopf et al, 2011;Lewis et al, 2009) which dealt with the optical growth of slightly absorbing particles. Hasenkopf et al (2011) focused on the optical growth at 532 nm of organic particles likely to have been present on early Earth and Titan, and Lewis et al (2009) studied the scattering and absorption increase (or reduction) at 530 and 870 nm using three different types of smoke particles.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Garland et al (2007) parameterized the relative humidity dependence of light extinction at 532 nm for inorganic ammonium sulfate aerosols, Baynard et al (2006) looked at mixtures of NaCl and ammonium sulfate with a few dicarboxylic acids, and Fierz-Schmidhauser et al (2010) measured the scattering dependence of ammonium sulfate and sodium chloride. Conversely, we could only find two recent studies (Hasenkopf et al, 2011;Lewis et al, 2009) which dealt with the optical growth of slightly absorbing particles. Hasenkopf et al (2011) focused on the optical growth at 532 nm of organic particles likely to have been present on early Earth and Titan, and Lewis et al (2009) studied the scattering and absorption increase (or reduction) at 530 and 870 nm using three different types of smoke particles.…”
Section: Introductionmentioning
confidence: 95%
“…Conversely, we could only find two recent studies (Hasenkopf et al, 2011;Lewis et al, 2009) which dealt with the optical growth of slightly absorbing particles. Hasenkopf et al (2011) focused on the optical growth at 532 nm of organic particles likely to have been present on early Earth and Titan, and Lewis et al (2009) studied the scattering and absorption increase (or reduction) at 530 and 870 nm using three different types of smoke particles.…”
Section: Introductionmentioning
confidence: 95%
“…For a non-spherical particle, such as a fresh soot agglomerate, the mobility diameter (D mob ) as measured by a DMA is normally larger than the geometric volume/mass equivalent diameter (D ve ) (DeCarlo et al, 2004). However, it has been widely reported that the coating on soot aggregates will modify its morphology (Weingartner et al, 1997;Zhang et al, 2008;Lewis et al, 2009;Pagels et al, 2009;Kiselev et al, 2010) by causing the soot aggregate to collapse and to become less fractal and more compact. The modification of the particle morphology will change its physical mobility properties, and therefore measurements of D mob .…”
Section: Htdma-sp2 Systemmentioning
confidence: 99%
“…by exposing hygroscopic soot to elevated RH conditions will cause enhanced reconstruction effect (i.e. Lewis et al, 2009). The undermined shape effect on ρ eff leads to a challenge in explicitly explaining the hygroscopic growth of BC particles.…”
Section: Growth Factor Modellingmentioning
confidence: 99%
“…We use the extinction-minus-scattering method in our lab. For highly absorbing particles, such as BC, this method is quite reasonable (Bond and Bergstrom, 2006), as it has been shown elsewhere (Lewis et al, 2009;Langridge et al, 2013) that PAS can include large errors under certain conditions. Additionally, our CRDS uses tunable lasers that provide a wide range of solar wavelengths (Singh et al, 2016), while most studies are limited to a single or a few specific wavelengths.…”
mentioning
confidence: 99%